Scientific Opinion on a Quantitative Microbiological Risk Assessment of Salmonella in slaughter and breeder pigs - EFSA Panel on Biological Hazards (BIOHAZ) (EFSA Journal, 2010)
Abstract This Quantitative Microbiological Risk Assessment (QMRA) represents a major step forward in terms of modelling Salmonella in pigs from farm to consumption as it takes into account the variability between and within EU Member States (MSs). Around 10–20% of human Salmonella infections in EU may be attributable to the pig reservoir as a whole. From the QMRA analysis it appears that an 80% or 90% reduction of lymph node prevalence should result in a comparable reduction in the number of human cases attributable to pig meat products. Theoretically, according to the QMRA the following scenarios appear possible (a) by ensuring that breeder pigs are Salmonella‐free a reduction of 70–80% in high prevalence MSs and 10–20% in low prevalence MSs can be foreseen; (b) by feeding only Salmonella‐free feedstuffs, a reduction of 10–20% in high prevalence MSs and 60–70% in low prevalence MSs can be foreseen; and (c) by preventing infection from external sources of Salmonella (i.e. rodents and birds) a reduction of 10–20% in slaughter pig lymph node prevalence can be foreseen in both high and low prevalence MSs. A hierarchy of control measures is suggested ‐ a high prevalence in breeder pigs needs to be addressed first, followed by control of feed and then control of environmental contamination. Also according to the QMRA, for each MS, a reduction of two logs (99%) of Salmonella numbers on contaminated carcasses would result in more than 90% reduction of the number of human salmonellosis cases attributable to pig meat consumption. The control of Salmonella in pig reservoir in the EU is a reasonable objective. The EU Salmonella control strategy in pigs should be continuously evaluated to identify possible improvements.